ICRISAT Empowers Participants from the Global South Countries through ITEC Courses - Kumar, Shalander; Afari-Sefa, Victor (International Crops Research Institute for the Semi-Arid Tropics, 2025)
ICRISAT launched the first in a series of international training programs on 20 January 2025 to equip decision-makers with tools to scale climate-resilient and sustainable farming systems. The training program, which concluded on 31 January 2025, is supported by the Indian Technical and Economic Cooperation (ITEC) - Government of India program. It spotlights South-South collaboration and adopts the 'Systems Approach' and tools for addressing agricultural challenges under the aegis of the CGIAR Science Program on Sustainable Farming.